How Will Ageing Affect Finland? - Antolín, Pablo (OECD Publishing, 2001)
In Finland, as in most OECD countries, the ageing of the population is one of the major long-term policy challenges. This paper first explores the scale of the demographic changes in Finland, the relevant institutions and their effect on the decision to retire. In light of the increase in the number of elderly expected over the coming years, various issues concerning their economic position and health care are considered. The paper then considers the impact that demographic changes will have on public finances: the cost of the pension system will increase by a third; health care spending and the cost of care for the frail elderly are also likely to rise substantially. The paper ends by outlining the policy options to copy with ageing ...
Keywords: Economics; Finland